Cytomegalovirus (CMV) epitope-specific CD4(+) T cells are inflated in HIV(+) CMV(+) subjects - Abana, CO; Pilkinton, MA; Gaudieri, S; Chopra, A; McDonnell, WJ; Wanjalla, C; Barnett, L; Gangula, R; Hager, C; Jung, DK; Engelhardt, BG; Jagasia, MH; et al. (American Association of Immunologists, 2017)
Select CMV epitopes drive life-long CD8(+) T cell memory inflation, but the extent of CD4 memory inflation is poorly studied. CD4(+) T cells specific for human CMV (HCMV) are elevated in HIV(+) HCMV(+) subjects. To determine whether HCMV epitope-specific CD4(+) T cell memory inflation occurs during HIV infection, we used HLA-DR7 (DRB1*07:01) tetramers loaded with the glycoprotein B DYSNTHSTRYV (DYS) epitope to characterize circulating CD4(+) T cells in coinfected HLA-DR7(+) long-term nonprogressor HIV subjects with undetectable HCMV plasma viremia. DYS-specific CD4(+) T cells were inflated among these HIV(+) subjects compared with those from an HIV(-) HCMV(+) HLA-DR7(+) cohort or with HLA-DR7-restricted CD4(+) T cells from the HIV-coinfected cohort that were specific for epitopes of HCMV phosphoprotein-65, tetanus toxoid precursor, EBV nuclear Ag 2, or HIV gag protein. Inflated DYS-specific CD4(+) T cells consisted of effector memory or effector memory-RA(+) subsets with restricted TCRβ usage and nearly monoclonal CDR3 containing novel conserved amino acids. Expression of this near-monoclonal TCR in a Jurkat cell-transfection system validated fine DYS specificity. Inflated cells were polyfunctional, not senescent, and displayed high ex vivo levels of granzyme B, CX3CR1, CD38, or HLA-DR but less often coexpressed CD38(+) and HLA-DR(+) The inflation mechanism did not involve apoptosis suppression, increased proliferation, or HIV gag cross-reactivity. Instead, the findings suggest that intermittent or chronic expression of epitopes, such as DYS, drive inflation of activated CD4(+) T cells that home to endothelial cells and have the potential to mediate cytotoxicity and vascular disease.